Angola Poverty Assessment - World Bank (World Bank, Washington, DC, 2020)
Angola is the third-largest economy in the Sub-Saharan Africa and is classified as a low-middle income economy. The incidence of poverty in Angola as of 2019 based on a monetary measure of welfare (monthly food and non-food consumption expenditures per adult equivalent) is 32.3 percent at the national level. The incidence of poverty rates is almost three times higher in rural areas (54.7 percent) than in urban areas (17.8 percent). The strong dichotomy in welfare between urban and rural areas in Angola is reflected in a large inequality at the national level. The Gini coefficient in Angola is 0.51 which is one of the highest in Africa. The duality of the Angolan economy is also reflected in two very different types of poverty. On the one hand, there is a traditional rural sector dominated by low-productivity subsistence agriculture. On the other hand, there is a modern export-oriented oil-economy, which is mostly concentrated in Luanda and some other urban centers. Accessibility also appears to play a key role in food security. In areas connected by road, the number of months in which a household experiences food shortage is strongly correlated with the number of months in which the road is usable.